PENERAPAN MODEL PICTURE AND PICTURE UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI KELAS III SEKOLAH DASAR - Rista, Florentina Ella; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to improve the implementation of learning to write poetry using the picture and picture model and improve poetry writing skills using picture and picture media in class III of State Elementary School 03 Pontianak City . The method used in this research is a descriptive method. This form of research is class action research with 3 cycles of treatment with stages of planning, implementation, observation, and reflection. The results that want to be achieved are valid data, accurate, accountable about the improvement of poetry writing skills using picture and picture model in Negeri 03 Pontianak Elementary School City that will be presented in the form of data Research results. The research Setting is conducted in the IIIC class of elementary School 03 Pontianak City. The results of his research are as follows: Increased teacher's ability to perform cycle I learning is on average 2.86, cycle II was obtained on average 3.43, and cycle III was obtained on average 3.81. Increased student writing skills on the I cycle gained an average of 61.66, cycle II gained an average of 68.67, and cycle III gained an average of 76.61. Â Keywords: Improve, Poetry Writing Skills, Picture and Picture Models